Satellite-Based Assessment of Nitrogen Dioxide Emissions from Libyan Power Plants: 2023 Annual Analysis (Journal of Humanitarian and Applied Sciences, 2025)
Nitrogen dioxide (NO2) is a major atmospheric pollutant with severe implications for human health and the environment. This study utilizes the TROPOspheric Monitoring Instrument (TROPOMI) aboard the Sentinel-5P satellite, accessed via Google Earth Engine (GEE), to analyse NO2 levels across Libya during 2023. The analysis reveals significant spatial and temporal variations in NO2 vertical column densities, identifying power plants in urban hubs such as Tripoli, Benghazi, and Misrata as primary emission sources. Seasonal trends show a marked elevation in pollution during the summer, with concentrations peaking in June at 7.01 x 10-5 (mol/m2), representing an 18.4% increase relative to the annual mean. These spikes are driven by increased energy demand, enhanced photochemical reactions, and meteorological conditions. The findings emphasize the critical need for targeted interventions, specifically recommending the retrofitting of power plants with selective catalytic reduction (SCR) systems and the diversification of the energy portfolio through investment in solar and wind infrastructure to reduce fossil fuel dependence.
Keywords: Nitrogen dioxide; satellite monitoring; power plants